Development of an admission criterion framework for high-cost medical consumables in governmental hospitals: a systematic review - Tianshu Chu; Yahui Han; Haiyin Wang (BMC, 2024)
Abstract Background High-cost medical consumables (HMCs) have emerged as significant economic and technological challenges for numerous national healthcare systems. Governmental hospitals play an indispensable role in many national health systems, closely linked to the evaluation of admissions and the management of procurement for HMCs. Nevertheless, many governmental hospitals face avoidable management risks due to the lack of a decision-making tool. In response, we conducted a systematic review to establishing a framework for the admission criteria of HMCs. This framework aims to enhance their effective utilization and maximize economic, clinical, and social benefits. Methods In accordance with a systematic review protocol developed for our study, we conducted comprehensive searches in the PubMed, Web of Science, and Embase databases to identify all correlation studies conducted prior to December 31, 2021. Subsequently, two independent reviewers performed a two-round screening process, resulting in the inclusion of 23 articles in our study. Finally, a third reviewer meticulously examined the selected indicators and contributed to the development of the final criterion framework. Results The criterion framework was established with 7 first-level indicators and 23 s-level indicators. Among the first-level indicators, "Clinical Benefit" held the highest significance, with a combined weight of 1.606, followed by "Economic Value" and "Organizational Impact" at 1.497 and 1.159, respectively. At the second level, "Safety" and "Efficacy" carried equal weight in the decision-making tool, with combined weights of approximately 1.300 each and a standard combined weight of 0.130. Conclusion This admission criteria framework serves as a vital decision-making tool for managing admissions and highlights several crucial evaluation indicators. Economic considerations emerge as the principal determinant in HMCs procurement decisions. Consequently, healthcare managers and decision-makers are recommended to give precedence to value-based healthcare and evidence-based procurement practices. In the long term, governmental hospitals must grapple with the challenge of judiciously allocating limited resources to maximize both social and economic benefits.